Faces of evil: unmasking the world's most despicable serial killers - Utton, Dominic (Michael O'Mara Books Limited, 2024)
"Uncover the chilling true stories behind some of history's most monstrous murderers. Ian Brady and Myra Hindley Ted Bundy, Harold Shipman - these notorious names represent the worst of humanity, men and women who are driven by an urge to kill, and kill again. They are monsters lurking among us, often living outwardly respectable lives while indulging their horrific desires under cover of darkness, or anonymity. Serial killers continue to hold a gruesome fascination, their crimes and compulsions seemingly incomprehensible to civilized society. Some have become household names, the subject of hit Netflix documentaries and BBC dramas ... others remain a hidden horror in the shadows. Organised thematically according to each killer's twisted passion, Faces of Evil chronicles the crimes of twenty of the most infamous - and less well-known - serial killers of the late twentieth and early twenty-first centuries, unpicking their means, motives and methods ... and attempting to understand what drove their horrific lust for murder"--Publisher's description